129THE WALKING STROOP–A NOVEL TEST FOR EXECUTIVE FUNCTION IN PARKINSON'S DISEASE. (June 2014) - Powell, E.; Jones, S.; Pampolini-Roberts, O.; Rees, D.; Hindle, J.
Abstract : Introduction: Parkinson's disease (PD) affects about 127, 000 patients in the UK and its prevalence is set to rise. Executive function and dual-tasking are impaired in Parkinson's disease dementia and non-demented PD patients. A Walking Stroop is a novel task designed to test executive function and dual-tasking. It combines a Stroop task and a 6m walk. We aim to ascertain whether there is any difference between PD participants and controls in Walking Stroop performance and to determine whether the 'Walking Stroop' tests executive function, dual tasking or both. Methods: Twenty PD patients and 20 controls completed a 6m walk, a congruent Walking Stroop condition (reading colour-names on the congruent side) and two incongruent Walking Stroop conditions (reading colour-names and naming ink colour on the incongruent side). Scores were compared to trail-making task and computerised Stroop performance, as well as mini mental state examination and Unified Parkinson's Disease Rating Scale scores. Results: There was no significant difference in Walking Stroop performance between PD patients and controls. There was a significant correlation (r = -0.704, n = 40, p = 0.000) between Walking Stroop and Trail Making Test Scaled Score, which measures executive function and dual-tasking. There was no correlation between Walking Stroop and Trail Making Test Ratio or Walking Stroop and computerised Stroop – both these tasks test executive function only. Conclusion: The Walking Stroop was found to test a combination of executive function and dual-tasking but not executive function alone. The Walking Stroop could have future use as a clinical screening test for falls risk pending further validation.